Corrosion Studies On Ss-321 In Natrium-Hydroxide Solution - S., Marzuki; Jodi, Heri; Effendi, Nurdin (MESIN, 2007)
Corrosion Studies On Ss-321 In Natrium-Hydroxide Solution. Experimental corrosionstudies on commercial SS-321 have been carried out. The experiments were carried out in a sodiumhydroxide medium with a concentration variation of 0.4 M. 0.5 M, 0.6 M, and0.7Mcorresponding topHvalues of 13.6, 13.69, 13.78, and 13.84 respectively. The experiments were carried out using a type ofM-273 EG&Gpotentiostat/galvanometer test instrument. The post-corrosion samples microstructure wereanalyzed with the aid of EDS (energy dispersive spectroscopy) equipped SEM instrument to detect thepresence of any viable corrosion byproducts. Forfurther verification x-ray diffraction method was alsoused to detect any possible emerging corrosion byproducts on the samples surfaces correlated to theSEM-EDS result. Experimental results confirm that A1SI-321 commercial alloys immersed in a natriumhydroxide corrosion medium with a variation of concentration experience very little or almost nocorrosion, so that according to the so-called Fontanas criteria these test-materials turn out to have anexcellent resistance toward natrium hydroxide corrosion. This is also evidenced by the very low corrosionrate value measured in this study. EDS study and X-ray diffraction results indicate that the possibleensuing corrosion byproducts are iron oxides, chromeoxides and silicon oxides.